MODERNIZING CERTIFICATES. (The Accounting Review, 1931)
Abstract This article focuses on the editor's views about the significance of corporate's financial statement. The editor says that records of the company both in the books and elsewhere is a curious expression, the last six words of which constitute another questionable pleonasm. In the everyday language of the auditor, the "records" are the books of account, documents and files. The reader of the certificate has the right to expect a term to be all-inclusive if it is not explicitly limited, there would seem to be no need of telling him the obvious. Besides, the auditor, for a portion of his information, goes beyond the records of the company during the course of his examination, if he did not do so, he would undoubtedly be guilty of negligence. Perhaps it was meant that the auditor has made some of his customary verifications "elsewhere" than in the records, but the language used falls short of saying so. Condition of affairs apparently is meant to convey the idea of "balance sheet" and "statement of profit and loss" as it stands it brings to mind "statement of affairs" and is confusing.